Being a nursing worker in a Sterile Processing Department: a phenomenological approach - Lopes, Dolores Ferreira de Melo; Silva, Arlete; Garanhani, Mara Lúcia; Merighi, Miriam Aparecida Barbosa (Revista da Escola de Enfermagem da USP, 2007)
This study investigated the experience of nursing workers at the Sterile Processing Department (SPD) of a hospital in Londrina, State of Paraná, using the qualitative phenomenological method. Ten interviews were conducted. The analysis of the discourses made possible to build four categories: 1) How the individual came to be part of the department - describes the various ways one may come to work in the unit; 2) Speaking about the work involved in the SPD - describes the turnover, the multiple simultaneous tasks that must be performed and the preference for certain areas; the closed atmosphere; the technological evolution; and the interpersonal relationships; 3) Dealing with difficulties - describes the daily routine; the repetitive and monotonous work; the physical exhaustion; the lack of supplies and equipment; the adjustment period; and the under-appreciation, discrimination, and ignorance of other health workers about their work; 4) Overcoming the obstacles - reveals that through greater aware-ness of their role in the Department these professionals are able to recognize their importance.